After recovery: towards resilience - Guida, Carmen (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts: Urban planning Literature Review; Town Planning International Rules and Legislation Overview; Urban Practices, Projects, and Innovative Approach; Framework of Scientific News and Events; Economy, Business and Land Use. Each of these sections examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban Planning Literature Review section aims at presenting recent books and journals, within global scientific panorama, on selected topics and issues. This contribution aims at discussing the main impacts and consequences of the Covid-19 pandemic on our lives and urban systems. While for the last issue of TeMA, this section of the journal was dedicated to the emergency phase, according to the new policy and strategic actions aimed at improving the coexistence of the new coronavirus within urban environments, this contribution is focused on how policy makers can enhance urban resilience, in sight of potential new health crisis.